Morbid obesity, multiple long-term conditions, and health-related quality of life among Australian adults: Estimates from three waves of a longitudinal household survey - Syed Afroz Keramat; Khorshed Alam; Byron Keating; Bright Opoku Ahinkorah; Richard Gyan Aboagye; Abdul-Aziz Seidu; Nandeeta Samad; Monidipa Saha; Jeff Gow; Stuart J.H. Biddle; Tracy Comans (Preventive Medicine Reports, 2022)
This study aims to investigate the impact of morbid obesity and multiple long-term conditions (MLTCs) on health-related quality of life (HRQoL). Data for this study were sourced from three waves (waves 9, 13 and 17) of the Household, Income and Labour Dynamics in Australia (HILDA) survey. The paper analyses 37,887 person-year observations from 19,387 individuals during the period 2009–2017. The longitudinal random-effects Tobit model was fitted to examine the association between morbid obesity, MLTCs and HRQoL. This study found that morbid obesity and MLTCs were both negatively associated with HRQoL as measured through physical component summary (PCS), mental component summary (MCS), and the short-form six-dimension utility index (SF-6D) of the 36-item Short-Form Health Survey (SF-36). Morbidly obese scored lower points on the PCS (β = −5.05, 95% CI: −5.73, −4.37), MCS (β = −1.03, 95% CI: −1.84, −0.23), and in the SF-6D utility index (β = −0.045, 95% CI: −0.054, −0.036) compared to their healthy weight counterparts. Similar findings were observed for individuals with MLTCs, with lower scores for the PCS (β = −4.79, 95% CI: −5.20, −4.38), MCS (β = −4.95, 95% CI: −5.43, −4.48), and SF-6D utility (β = −0.071, 95% CI: −0.076, −0.066). Additionally, multiplicative interaction between morbid obesity and MLTCs was observed to modestly exacerbated the negative effect of morbid obesity on PCS scores (β = −1.69, 95% CI: −2.74, −0.64). The interaction effect, on the other hand, significantly lessen the unfavourable effect of morbid obesity on the MCS score (β = 1.34, 95% CI: 0.10, 2.58). The findings of this study will be useful for future cost-effectiveness analyses and measuring the burden of diseases since it provides information on the disutility associated with morbid obesity and MLTCs.